A unified strain-hardening and strain-softening elastoplastic constitutive model for intact rocks. (August 2022) - Xiao, Yingming; Qiao, Yafei; He, Manchao; Li, Hongru; Cheng, Tai; Tang, Jie
Abstract: A unified strain-hardening and strain-softening (UHS) elastoplastic constitutive model is developed to capture the nonlinearity of intact rocks. Three new developments are incorporated into the model: (i) a unified strain-hardening and strain-softening rule, which is used to describe the nonlinearity of the stress–strain curve; (ii) the cohesion loss model, which can describe the nonlinearity of the residual strength; and (iii) normalized plastic shear strain, which is adopted as the plastic internal variable. There are 15 model parameters. All of them can be easily obtained by uniaxial compression tests and triaxial tests under different confining pressures. The proposed model has been implemented in FLAC3D and validated against five different types of rocks. The results show that the model can capture the nonlinearity of the stress–strain curve, including both the strain-hardening stage before the peak strength and the strain-softening at the post-peak stage. The model is also able to describe the effects of the confining pressure on the peak strength, residual strength and stress–strain curve. Moreover, the transition from brittle failure to ductile failure under high confining pressure can be well described.